Bears at the door. (Economist, 2010)
the article focuses on the cellular telephone manufacturer Nokia. The company still leads in market share for smartphones, the fastest-growing part of the cellular telephone marker, but is much less profitable than its competitors in that market, Apple Inc. and Research in Motion. The increasing importance of developing software for cellular telephones poses a challenge to company management.